The Future of Digital Sequence Information for Plant Genetic Resources for Food and Agriculture - Aubry, Sylvain (Frontiers in Plant Science, 2019)
Anyone familiar with modern biology may find peculiar the ongoing international debates on the legal status of “Digital Sequence Information” (DSI). Indeed, a large majority of recent advances in biology, medicine or agriculture were achieved by sharing and mining of freely accessible sequencing data. It is most probably because of the tremendous success of modern genomics and advances of synthetic biology that concerns were raised about possible fair and equitable ways of sharing data. The DSI concept is relatively new and all concerned parties agreed upon the need for a clear definition. For example, the extent to which DSI understanding is limited only to genetic sequence data has to be clarified. In this paper, I focus on a subset of DSI essential to humankind: the DSI originating from plant genetic resources for food and agriculture (PGRFA). Two international agreements shape the conservation and use of plant genetic resources: The Convention on Biodiversity and the International Treaty for Plant Genetic Resources for Food and Agriculture. I will describe how the increasing amount of genomic data, information and studies in particular for research, breeding and conservation interact with the existing legal framework at the global level. Using possible scenarios, I will emphasise the complexity of the issues surrounding DSI for PGRFA and try to provide potential ways forward for developing an inclusive governance and fair use of these genetic resources.